Construction of highly enantioenriched spirocyclopentaneoxindoles containing four consecutive stereocenters via thiourea-catalyzed asymmetric Michael–Henry cascade reactions - Du, Yonglei; Li, Jian; Chen, Kerong; Wu, Chenglin; Zhou, Yu; Liu, Hong (Beilstein Journal of Organic Chemistry, 2017)
The thiourea-catalyzed asymmetric synthesis of highly enantioenriched spirocyclopentaneoxindoles containing chiral amide functional groups using simple 3-substituted oxindoles and nitrovinylacetamide as starting materials was achieved successfully. This protocol features operational simplicity, high atom economy, and high catalytic asymmetry, thus representing a versatile approach to the synthesis of highly enantioenriched spirocyclopentaneoxindoles.
Keywords: asymmetric synthesis; four consecutive stereocenters; Michael–Henry cascade reactions; spirocyclopentaneoxindoles; thioureas

(untitled) - Sharma, N.; Li, Z.; Sharma, U. K.; Van der Eycken, E. V. (Org. Lett., 2014)

(untitled) - Ball-Jones, N. R.; Badillo, J. J.; Franz, A. K. (Org. Biomol. Chem., 2012)

(untitled) - Yu, J.; Shi, F.; Gong, L.-Z. (Acc. Chem. Res., 2011)

(untitled) - Zhou, F.; Liu, Y.-L.; Zhou, J. (Adv. Synth. Catal., 2010)

(untitled) - Rottmann, M.; McNamara, C.; Yeung, B. K. S.; Lee, M. C. S.; Zou, B.; Russell, B.; Seitz, P.; Plouffe, D. M.; Dharia, N. V.; Tan, J.; Cohen, S. B.; Spencer, K. R.; et al. (Science, 2010)

(untitled) - Antonchick, A. P.; Gerding-Reimers, C.; Catarinella, M.; Schuermann, M.; Preut, H.; Ziegler, S.; Rauh, D.; Waldmann, H. (Nat. Chem., 2010)

(untitled) - Shangary, S.; Qin, D.; McEachern, D.; Liu, M.; Miller, R. S.; Qiu, S.; Nikolovska-Coleska, Z.; Ding, K.; Wang, G.; Chen, J.; Bernard, D.; Zhang, J.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Periyasami, G.; Raghunathan, R.; Surendiran, G.; Mathivanan, N. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Mohr, J. T.; Krout, M. R.; Stoltz, B. M. (Nature, 2008)

(untitled) - Fensome, A.; Adams, W. R.; Adams, A. L.; Berrodin, T. J.; Cohen, J.; Huselton, C.; Illenberger, A.; Kern, J. C.; Hudak, V. A.; Marella, M. A.; Melenski, E. G.; McComas, C. C.; et al. (J. Med. Chem., 2008)

(untitled) - Galliford, C. V.; Scheidt, K. A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Marti, C.; Carreira, E. M. (Eur. J. Org. Chem., 2003)

(untitled) - Mercado-Marin, E. V.; Garcia-Reynaga, P.; Romminger, S.; Pimenta, E. F.; Romney, D. K.; Lodewyk, M. W.; Williams, D. E.; Andersen, R. J.; Miller, S. J.; Tantillo, D. J.; Berlinck, R. G. S.; Sarpong, R. (Nature, 2014)

(untitled) - Pimenta, E. F.; Vita-Marques, A. M.; Tininis, A.; Seleghim, M. H. R.; Sette, L. D.; Veloso, K.; Ferreira, A. G.; Williams, D. E.; Patrick, B. O.; Dalisay, D. S.; Andersen, R. J.; Berlinck, R. G. S. (J. Nat. Prod., 2010)

(untitled) - McIver, A. L.; Deiters, A. (Org. Lett., 2010)

(untitled) - Trost, B. M.; Brennan, M. K. (Synthesis, 2009)

(untitled) - Greshock, T. J.; Grubbs, A. W.; Jiao, P.; Wicklow, D. T.; Gloer, J. B.; Williams, R. M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Mugishima, T.; Tsuda, M.; Kasai, Y.; Ishiyama, H.; Fukushi, E.; Kawabata, J.; Watanabe, M.; Akao, K.; Kobayashi, J. (J. Org. Chem., 2005)

(untitled) - Bond, R. F.; Boeyens, J. C. A.; Holzapfel, C. W.; Steyn, P. S. (J. Chem. Soc., Perkin Trans. 1, 1979)

(untitled) - Hong, L.; Wang, R. (Adv. Synth. Catal., 2013)

(untitled) - Singh, G. S.; Desta, Z. Y. (Chem. Rev., 2012)

(untitled) - Cheng, D.; Ishihara, Y.; Tan, B.; Barbas, C. F., III (ACS Catal., 2014)

(untitled) - Zhou, B.; Yang, Y.; Shi, J.; Luo, Z.; Li, Y. (J. Org. Chem., 2013)

(untitled) - Shi, Y.; Lin, A.; Mao, H.; Mao, Z.; Li, W.; Hu, H.; Zhu, C.; Cheng, Y. (Chem. – Eur. J., 2013)

(untitled) - Albertshofer, K.; Tan, B.; Barbas, C. F., III (Org. Lett., 2012)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Sun, W.; Zhu, G.; Wu, C.; Hong, L.; Wang, R. (Chem. – Eur. J., 2012)

(untitled) - Li, Y.-M.; Li, X.; Peng, F.-Z.; Li, Z.-Q.; Wu, S.-T.; Sun, Z.-W.; Zhang, H.-B.; Shao, Z.-H. (Org. Lett., 2011)

(untitled) - Trost, B. M.; Cramer, N.; Silverman, S. M. (J. Am. Chem. Soc., 2007)

(untitled) - Corkey, B. K.; Toste, F. D. (J. Am. Chem. Soc., 2007)

(untitled) - Parthasarathy, K.; Praveen, C.; Jeyaveeran, J. C.; Prince, A. A. M. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Arai, T.; Miyazaki, T.; Ogawa, H.; Masu, H. (Org. Lett., 2016)

(untitled) - Dhara, K.; Mandal, T.; Das, J.; Dash, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ding, L.-Z.; Zhong, T.-S.; Wu, H.; Wang, Y.-M. (Eur. J. Org. Chem., 2014)

(untitled) - Albertshofer, K.; Anderson, K. E.; Barbas, C. F., III (Org. Lett., 2012)

(untitled) - Zhang, S. L.; Xie, H.-X.; Zhu, J.; Li, H.; Zhang, X.-S.; Li, J.; Wang, W. (Nat. Commun., 2011)

(untitled) - Wang, Y.; Liu, L.; Zhang, T.; Zhong, N.-J.; Wang, D.; Chen, Y.-J. (J. Org. Chem., 2012)

(untitled) - Doyle, A. G.; Jacobsen, E. N. (Chem. Rev., 2007)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Voituriez, A.; Pinto, N.; Neel, M.; Retailleau, P.; Marinetti, A. (Chem. – Eur. J., 2010)

(untitled) - Pinto, N.; Neel, M.; Panossian, A.; Retailleau, P.; Frison, G.; Voituriez, A.; Marinetti, A. (Chem. – Eur. J., 2010)

(untitled) - Zhang, J.; Cao, D.; Wang, H.; Zheng, C.; Zhao, G.; Shang, Y. (J. Org. Chem., 2016)

(untitled) - Zhang, X.-Y.; Shen, Z.; Hu, L.-L.; Wang, L.-J.; Lin, Y.-S.; Xie, J.-W.; Cui, H.-L. (Tetrahedron Lett., 2016)

(untitled) - Voituriez, A.; Marinetti, A.; Gicquel, M. (Synlett, 2015)

(untitled) - Peng, J.; Huang, X.; Jiang, L.; Cui, H.-L.; Chen, Y.-C. (Org. Lett., 2011)

(untitled) - Jiang, K.; Tiwari, B.; Chi, Y. R. (Org. Lett., 2012)

(untitled) - Grossmann, A.; Enders, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Menon, R. S.; Biju, A. T.; Nair, V. (Chem. Soc. Rev., 2015)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (Nat. Chem., 2011)

(untitled) - Li, X.; Li, Y.-M.; Peng, F.-Z.; Wu, S.-T.; Li, Z.-Q.; Sun, Z.-W.; Zhang, H.-B.; Shao, Z.-H. (Org. Lett., 2011)

(untitled) - Zhu, S.; Yu, S.; Ma, D. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wiesner, M.; Revell, J. D.; Wennemers, H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wiesner, M.; Revell, J. D.; Tonazzi, S.; Wennemers, H. (J. Am. Chem. Soc., 2008)

(untitled) - Hayashi, Y.; Itoh, T.; Ohkubo, M.; Ishikawa, H. (Angew. Chem., Int. Ed., 2008)

(untitled) - García-García, P.; Ladépêche, A.; Halder, R.; List, B. (Angew. Chem., Int. Ed., 2008)

(untitled) - McCooey, S. H.; Connon, S. J. (Org. Lett., 2007)

(untitled) - Xu, Y.; Zou, W.; Sundén, H.; Ibrahem, S.; Córdova, A. (Adv. Synth. Catal., 2006)

(untitled) - Wang, J.; Li, H.; Lou, B.; Zu, L.; Guo, H.; Wang, W. (Chem. – Eur. J., 2006)

(untitled) - Palomo, C.; Vera, S.; Mielgo, A.; Gómez-Bengoa, E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Mossé, S.; Alexakis, A. (Org. Lett., 2006)

(untitled) - Luo, S.; Mi, X.; Zhang, L.; Liu, S.; Xu, H.; Cheng, J.-P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Wang, W.; Wang, J.; Li, H. (Angew. Chem., Int. Ed., 2005)

(untitled) - Hayashi, Y.; Gotoh, H.; Hayashi, T.; Shoji, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Andrey, O.; Alexakis, A.; Tomassini, A.; Bernardinelli, G. (Adv. Synth. Catal., 2004)

(untitled) - Cai, H.; Zhou, Y.; Zhang, D.; Xu, J.; Liu, H. (Chem. Commun., 2014)

(untitled) - Rong, X.; Yao, H.; Xia, W.; Du, Y.; Zhou, Y.; Liu, H. (ACS Comb. Sci., 2016)

(untitled) - Chen, X.; Chen, H.; Ji, X.; Jiang, H.; Yao, Z.-J.; Liu, H. (Org. Lett., 2013)

(untitled) - Yao, H.; Zhou, Y.; Chen, X.; Zhang, P.; Xu, J.; Liu, H. (J. Org. Chem., 2016)

(untitled) - Okino, T.; Hoashi, Y.; Furukawa, T.; Xu, X.; Takemoto, Y. (J. Am. Chem. Soc., 2005)